المعزولة من اصابات سريرية مختلفة لبعض المضادات الحيوية Pseudomonas aeruginosa مقاومة جرثومة - مهدي عريبي سناء (University of Thi-Qar Journal of Science, 2010)
This study was conducted for the isolation and identification of P.aeruginosa from different clinical cases. The total number of samples were 129 sample wounds; burns; urinary tract ; chronic otitis media infections and were collected from and detection of their susceptibility for 15 antibiotic .The total number of isolated and confirmed P.aeruginosa were 38 out from 129 samples. The distribution of positive isolates were 12 from 38 cases otisit infections ; 8 from 19 samples of burnes ; 10 from 50 samples of urin ;8 from 22 samples of wounds .All isolates show A high perecentage of resistance (100%) aginst penicillin and ampicillin .the lower resistance was registrated aginst Amikacin (30%), azthromycin (22%) ;ciprofloxacin (18%). According to the results our isolates were in consistent with what is called Multi Drug Resistant P.aeruginosa ( MDRPA) .The results of this study show that sex ;age and proloned antimicrobial admistration were fundamental factoers in reasing the chance of infection .